The Application of P2P Lending Platform on MSMEs "GO Online Program" at NGALUP.CO - Sari, Andina Paramita; Ardianto, Yusaq Tomo; Prasetya, Dwi Arman (MEC-J (Management and Economics Journal), 2021)
Â This study aims to identify the characteristics and influence of the Self Efficacy, Social Influence, and Performance Expectancy variables on Behavioral Intention on MSME GO Online at Ngalup.co program in Malang City by utilizing the Peer to Peer (P2P) Lending Platform. This research is classified as an explanatory research, which is scientific research conducted to explain the relationship between the variables studied through hypothesis testing. Additionally, this study utilizes a quantitative form with the aim of examining the factors that influence the use of P2P Lending of Go Online Program at Ngalup.co. The TCR value falls into the high category which means that MSMEs who are members of the Ngalup.co Program in Malang City is classified as high. This means that respondents expect the use of the P2P lending system to produce output and increase work productivity. This study concludes that the respondents have the view regarding online loans as a promising platform for accessing capital for MSME businesses. Several cases indicate that online loans provide lower interest rates and risks, thus MSME business players are greatly assisted by low installments and interest.